(641) A Selected Annotated Bibliography of United Nations Publications and Documents on General and Methodological Aspects of Development Planning, 1955-1965 قائمة مختارة من المراجع المشروحة للمنشورات والمستندات التابعة للأمم المتحدة حول الجوانب العامة والمنهجية للتخطيط التنموي، 1955-1965 - ., UN Economic & Social Council (INP, 2024)
paper